User-Centered Design for E-commerce Prototyping - Risqia, Lutfi Windu; Astiti, Sarah (Journal of INISTA, 2024)
Re.wood is a wooden furniture business located in Tinggarjaya Village, Jatilawang District, Banyumas Regency that offers a variety of furniture products, ranging from chairs to wall hangings, to beautify interior and exterior spaces, but still has a limited market share. Re.wood currently uses a conventional sales process that is less effective and lacks information for customers, which causes a lack of sales levels for Re.wood. Designing a system before entering the system development stage is a must because it ensures that the resulting solution is relevant and effective in overcoming the problems users face. The problem can be solved by designing User Interface and User Experience of web-based e-commerce applications. The design method used by researchers is the user-centered design method. User-centered design is a method of focusing on the needs of potential users in the system design stage or process. The results of designing the user interface and user experience only include the user interface developed using Figma. The resulting website produces menus such as Home Page, login, Shop, Cart, Search, and Profile. This evaluation utilized the User Experience Questionnaire (UEQ) methodology to assess various aspects of the system. The resulting values (1.55 for Efficiency, 1.54 for Attractiveness, 1.49 for Clarity, 1.33 for Accuracy, 1.5 for Stimulation, and 1.15 for Novelty) represent the average UEQ calculation figures for each dimension. In other words, these numbers correspond to the results obtained through the UEQ, which helps evaluate user experience in terms of efficiency, attractiveness, clarity, accuracy, stimulation, and novelty. UEQ uses a Likert scale to measure user experience, and the resulting values show that the system performs well in most aspects. These findings indicate that the prototype meets the needs and provides a satisfying user experience.